IMPLEMENTASI PENYALURAN BANTUAN SOSIAL COVID-19 DI DKI JAKARTA - Roy Morado (Dialogue : Jurnal Ilmu Administrasi Publik, 2021)
The Covid-19 pandemic has caused the government, both central and regional, to be overwhelmed in distributing social assistance to the community. In Jakarta, it is known that there are residents who return social assistance because they feel they are not entitled to receive such assistance. In addition, many residents who should have received assistance but did not receive assistance due to beneficiary data problems. This study aims to identify and analyze the forms of implementation of the distribution of Covid-19 Social Assistance in DKI Jakarta. This study uses a qualitative approach with a literature study method using reference books and similar previous research results in order to obtain a theoretical basis for the problem to be studied. This study focuses on analyzing the implementation of the distribution of Covid-19 Social Assistance using the Mazmanian & Sabatier theory. The results of this study indicate that the distribution of COVID-19 social assistance is quite good, but has not covered all of the beneficiaries. There are problems related to the data on beneficiaries and the poor quality of basic food materials. The supporting factor for the distribution of COVID-19 social assistance in meeting the needs of vulnerable communities is the collaboration carried out by implementing officials with various other agencies. Public support is enthusiasm from the community and commitment from implementing officials. The inhibiting factor for the implementation of the distribution of COVID-19 social assistance is the confusion of data on beneficiaries that is out of sync between the central government and the data submitted by the local RT/RW.